PENGOLAHAN LIMBAH CAIR PABRIK KECAP SECARA KOAGULASI DAN FLOKULASI - Indriyati, Indriyati; Susanto, Joko Prayitno (Jurnal Teknologi Lingkungan, 2009)
Soya bean sauce waste water is a high organic wastewater and has dark color, thereforeit is difficult to degrade it biologically and also in getting clear color.Base on as mentioned above, it is tried to process it with coagulation and flocculationuse Aluminum sulfate and PAC which is added to wastewater with several dosesvariation of Alumunium sulfate: (100, 200, 300. 250) ppm and PAC with doses (50,100, 150, 200) ppm.Experiment result shows that the experiment which use Aluminum sulfate and PAC ascoagulant could give a good quality of processing and suitable with the threshold ofwastewater. The application of floculant Aquaklir 240 could help the performance ofcoagulant that can be seen from the turbidity, suspended solid and flock size form.